Beyond fight or flight: The need for conflict management training in medical education. (26th March 2018) - Cochran, Nan; Charlton, Paul; Reed, Virginia; Thurber, Peter; Fisher, Elliott
Abstract : This article reviewed the literature on conflict management training in medicine, proposed a set of competencies that health professionals need to learn in order to effectively deal with conflict in health care settings, and described a pilot project designed to teach many of these competencies at Dartmouth. Our review of the evidence, discussions with experts, and pilot findings highlight the potential value of incorporating comprehensive conflict management training in medical education. Further research is needed to evaluate the optimal timing and most effective ways to teach these skills in medical school, residency, and beyond.